2020
DOI: 10.1111/een.12980
|View full text |Cite
|
Sign up to set email alerts
|

Ant preference for seeds without awns increases removal of exotic relative to native grass seeds

Abstract: 1. The removal of seeds by granivorous ants can affect plant recruitment through either seed loss from predation or the dispersal and recruitment of seeds that are removed but not consumed. Consequently, variation in ant selection preferences can influence patterns of seed removal and affect plant community composition, including the spread of exotic plant species. 2. We conducted a seed removal experiment to determine whether: 1) rates of removal by ants differed between three native and three exotic grass sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…We found no evidence that plot contamination affected recruitment outcomes (Supporting information), possibly due to strong niche differentiation among our species. We did observe ants removing seeds during our experiment, and a separate experiment in the same grassland confirmed the preferential removal of exotic grass seeds by ant seed predators (Wandrag et al 2021). High rates of seed predation will strongly limit plant recruitment (Hulme 1994) and are common in grasslands globally (Turnbull et al 2000).…”
Section: Discussionsupporting
confidence: 85%
“…We found no evidence that plot contamination affected recruitment outcomes (Supporting information), possibly due to strong niche differentiation among our species. We did observe ants removing seeds during our experiment, and a separate experiment in the same grassland confirmed the preferential removal of exotic grass seeds by ant seed predators (Wandrag et al 2021). High rates of seed predation will strongly limit plant recruitment (Hulme 1994) and are common in grasslands globally (Turnbull et al 2000).…”
Section: Discussionsupporting
confidence: 85%
“…Morphology is another common driver of seed preference, and the ACHY and HEAN seeds preferred by P. occidentalis are morphologically similar, with smooth, awnless seed coats. This result supports recent studies that find lower ant granivory for seeds with a structure or coating (Crist & MacMahon 1992;Paolini et al 2020;Wandrag et al 2021) or a higher seed to seed plus structure ratio (Martyn et al 2022), possibly because large awns make seeds cumbersome for transport. In contrast, an older study by Pulliam and Brand (1975) found that Pogonomyrmex spp.…”
Section: Seed Preferencesupporting
confidence: 91%
“…Seed movement by granivores is likely an underestimated challenge for restoration success. Granivores can remove (predate) native seed spread on the landscape (Linabury et al 2019), assist native seed movement (Brewer & Rejmanek 1999), and even increase exotic seed movement (Ortiz et al 2021; Wandrag et al 2021). For grasslands, understanding and reducing ant‐seed predation could be important components of restoration success.…”
Section: Discussionmentioning
confidence: 99%
“…Our results compliment those of previous studies that showed a seed structure or coating can reduce seed predation by ants. For example, Wandrag et al (2021) conducted a comparative study with three exotic seed species naturally with no awns, three native seed species with awns intact, and the same three native species with the awns removed in an Australian grassland. They found that seed removal rate by ants was highest for the exotic species but that removing the awns increased these rates almost fivefold.…”
Section: Structure Impacts Seed Preferencementioning
confidence: 99%